Mechanics of nonplanar faults at extensional steps with application to the 1992 M 7.3 Landers, California, earthquake. Issue 6 (26th June 2013) - Madden, Elizabeth H.; Maerten, Frantz; Pollard, David D.
Abstract: [1] Earthquakes that rupture across steps between faults can be larger than those predicted from individual fault lengths, making understanding multifault events critical to assessing earthquake hazard. Empirical data from earthquake surface ruptures suggest that the distances between faults that rupture together can range from <1 to 5 km. Dynamic and quasi‐static models of planar faults determine similar distances. However, studies of interactions between realistic, 3‐D nonplanar faults are few. A general comparison of quasi‐static stress perturbations and triggering potentials with mechanical models incorporating either planar or nonplanar faults highlights the sensitivity of planar fault models to model parameters and reveals no clear relationship between mean fault slip and triggering potential. More specifically, planar fault models predict triggering across a 3 km extensional step, while models incorporating nonplanar faults indicate that a connecting fault is necessary to transfer slip through a 3 km step along the 1992 Landers, California earthquake rupture. The mechanical approach taken captures the stress changes as well as the total stress following fault slip, improving the criterion used to determine triggered failure potential. This underscores the need for additional constraint on fault strength and cohesion. The focus on complex fault geometry restricts analyses to the quasi‐static realm, limiting the results to fault interactions over the short distances and slow rupture velocities for which the quasi‐static stress field is relevant or approximates the dynamic stress field. Key Points: Models incorporating planar faults do not capture non‐planar fault interactions Mechanical models allow analyses of fault interactions to address fault strength A crossing fault may be necessary for slip across a 3 km step